2016
DOI: 10.1016/j.ecns.2015.12.001
|View full text |Cite
|
Sign up to set email alerts
|

Nursing Students as Epidemiologists: A Simulation Approach

Abstract: Simulation is commonly used in nursing education to teach clinical skills. Here, we describe the development processes, implementation, and evaluation of an epidemiology simulation used in a community and public health nursing undergraduate clinical course at the University of Pennsylvania. The simulation was designed to teach students the principles and concepts of outbreak investigation and was based on the 2003 Severe Acute Respiratory Syndrome outbreak in Toronto, Canada. The simulation places students in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 6 publications
0
4
0
Order By: Relevance
“…For simulation teaching in specific research design, an outbreak investigation simulation was developed to teach nursing students principles of epidemiology in 2016 [42]. A Korean study reported the feasibility and good effects of a course including a simulated clinical crossover trial to teach clinical studies for undergraduates, during which students were randomly grouped to distinguish between two different types of cola as simulated subjects [14].…”
Section: Discussionmentioning
confidence: 99%
“…For simulation teaching in specific research design, an outbreak investigation simulation was developed to teach nursing students principles of epidemiology in 2016 [42]. A Korean study reported the feasibility and good effects of a course including a simulated clinical crossover trial to teach clinical studies for undergraduates, during which students were randomly grouped to distinguish between two different types of cola as simulated subjects [14].…”
Section: Discussionmentioning
confidence: 99%
“…Nursing students are used to move themselves electronically in different interactive network environments. 27,45,46 This has led to that nursing studies are problem-free when education technology supports study work. Therefore, the study foundation needs to be quick, direct and enable an obstacle-free interaction between teachers and different actors in nursing education and healthcare organizations where nursing students encounter the clinical reality.…”
Section: Discussionmentioning
confidence: 99%
“…By mirroring the real-world clinical research process, research skills can be trained, including protocol design, recruitment, data collection and analysis, report writing and dissemination. Previous studies employed simulation in protocol development [ 14 ], principles and concepts of outbreak [ 15 ], research design [ 5 , 16 ]. However, comprehensive evidences on effectiveness of high-fidelity simulation for overall process of clinical researches is still limited.…”
Section: Introductionmentioning
confidence: 99%